"There are carers, and then there are carers who actually care"; Conceptualizations of care among looked after children and care leavers, social workers and carers. (June 2019) - Brown, Rebecca; Alderson, Hayley; Kaner, Eileen; McGovern, Ruth; Lingam, Raghu
Abstract: Background: Looked after children and care leavers (LACCL) are some of the most vulnerable and marginalized young people in our communities. Existing research demonstrates that this group often interprets care in terms of genuineness and tends to feel uncared for. Less work exists from the perspective of social workers and formal carers. Objective: This study aims to explore how care is perceived and practiced among LACCL and those with a duty of care for them. We use a theoretical lens of care ethics to compare and contrast understandings in order to explore how they affect the delivery and receipt of care. Participants & setting: There were 44 participants from four local authorities in north-east England including nineteen LACCL aged 12–20, eight social workers, and nineteen formal carers. Method: Twenty-eight semi-structured 1:1 interviews, four dyad interviews and three focus group interviews. Results: LACCL desired care that felt familial, went beyond minimum standards and involved understanding. Social workers had to manage LACCL expectations and build relationships by both rationing care according to role constraints whilst sometimes going 'above and beyond' statutory care. Carers conceptualized care in terms of dedication and discipline but felt limited in their ability to achieve care in this way. Conclusion: Bridging different conceptualizations of care is necessary to achieve integrated support for these vulnerable young people whilst also helping them to develop key skills for later adult life. A deeper understanding of frameworks of care has implications for social worker and formal carer training and practice.